Learning styles of the UUM distant learning students - Johari, Anita; Ku-Mahamud, Ku Ruhana; Mohd Alipiah, Fathilah (2000)
A study was conducted to examine the learning styles of the Universiti Utara Malaysia distant learning students.The study examined the students' background, management of time and commitment with their studies. Questionnaires were distributed to all UUM distant learning. Findings indicated that excellent students are from the auditory learners while bad performance students are those that are not committed with their studies. Nevertheless, majority of the students are found to be committed to their studies.There are students utilizing unidentified learning styles. Financial and lack of time to study are the main problems encountered by the students.